Pengembangan Model SIAP-GS Berbasis Google Sites untuk Kesiapan Dokumentasi Akreditasi Program Studi Manajemen Pendidikan - Rizqi Nur Afifah; Desi Rahmawati; Muhamad Fadholi; Gelar Gelora Mestika; Annisa Putri Alamsyah; Gustiandra Tri Saputra; Nashita Sabira Sahla (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study aimed to develop a Google Sites-based document management model tailored to the specific context of the Educational Management undergraduate program at the Faculty of Education, Universitas Negeri Jakarta, to strengthen its documentation readiness for accreditation under the Indonesian teacher-education accreditation instrument (IAPSK 3.0). This study is limited to documentation readiness specifically the extent to which accreditation evidence is structured, current, and traceable rather than overall accreditation readiness.Methods – A Research and Development approach following the ADDIE model was applied, limited to its first three stages: Analysis, Design, and Development. Data were collected through in-depth interviews with five key informants, four weeks of observation, and document study, then analyzed qualitatively with technique and source triangulation. To provide initial (formative) validation of the prototype rather than an Implementation or Evaluation stage a limited socialization was conducted with fourteen lecturers and education staff using a nineteen-item Likert questionnaire across four dimensions. Findings – The analysis showed that the real problem was not the absence of digital storage but the absence of structure, naming standards, and governance. The resulting model, named SIAP-GS, maps its information architecture directly onto the nine criteria and sixty-five elements of IAPSK 3.0, applies a single-source-multiple-views principle, and deliberately keeps technical complexity low. The prototype obtained an overall mean of 4.59 out of 5 (very good), with the highest score on the benefit-and-usefulness dimension.Research Implications – The study covers only the first three ADDIE stages and a single study program; the implementation and evaluation stages, wider testing, and long-term impact on actual accreditation outcomes remain agendas for further research.